LEARNING MEDIA INNOVATION THROUGH INDONESIAN SUBJECTS IN GRADE II ELEMENTARY SCHOOL - Amin Basri (JGK (Jurnal Guru Kita), 2024)
The phenomenon in school shows that in Indonesian Language learning there is still a tendency for teachers to be are using learning media or teaching aids. Teachers use makeshift or very simple media or props, which are far from attractive to attract student™s attention because they don™t pay attention to color composition, the size is not propotional, and they are not acquire Indonesia language concepts. There for, innovation is needed in learning Indonesian. The aim of this research is to find out what learning media innovations are used at SD Medan and to find out the influence of these learning media in learning Indonesian. This research is was conducted using qualitative methods. This research was carried out at SD Medan, the subjects of this research were teachers at SD Medan, and while the object was learning media innovation in Indonesian language subjects  at SD Medan. The data collection techniques used were interviews and literature. The research results obtained are learning media innovations in Indonesian subjects at SD Medan includes using picture media, puzzle media, videos and teachinga aids. Based on the results of interviews, the use of this media is very effective in learning Indonesian,student don™t feel bored while learning takes place.